2004
DOI: 10.1038/sj.bjc.6602149
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of epidermal growth factor receptor with related factors is associated with a poor prognosis in non-small-cell lung cancer

Abstract: The epidermal growth factor receptor (EGFR) is commonly expressed in non-small-cell lung cancer (NSCLC) and promotes a host of mechanisms involved in tumorigenesis. However, EGFR expression does not reliably predict prognosis or response to EGFR-targeted therapies. The data from two previous studies of a series of 181 consecutive surgically resected stage I -IIIA NSCLC patients who had survived in excess of 60 days were explored. Of these patients, tissue was available for evaluation of EGFR in 179 patients, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 34 publications
1
25
2
1
Order By: Relevance
“…Increased expression of EGFR has been shown in the majority of non -small cell lung cancers with overexpression in up to 85% of squamous cell lung carcinomas (23 -27). In some studies, EGFR overexpression has also been shown to have prognostic implications in lung cancer (28,29), whereas, in others, including studies from our institution, no significant association with prognosis was found (26). Bronchial dysplasia is believed to be the precursor of squamous cell lung carcinoma; thus, EGFR might play a significant role in the progression of these lesions to invasive cancer.…”
mentioning
confidence: 71%
“…Increased expression of EGFR has been shown in the majority of non -small cell lung cancers with overexpression in up to 85% of squamous cell lung carcinomas (23 -27). In some studies, EGFR overexpression has also been shown to have prognostic implications in lung cancer (28,29), whereas, in others, including studies from our institution, no significant association with prognosis was found (26). Bronchial dysplasia is believed to be the precursor of squamous cell lung carcinoma; thus, EGFR might play a significant role in the progression of these lesions to invasive cancer.…”
mentioning
confidence: 71%
“…10 Aberrant expression of TGF␣ or EGFR by tumors typically confers a more aggressive phenotype and is thus often predictive of poor prognosis. [11][12][13][14] Supported in part by SPORE in Prostate Cancer grant CA902701 from the National Cancer Institute.…”
mentioning
confidence: 99%
“…Overexpression of EGFR has been correlated with the poor prognosis of NSCLCs [23,24]. In the present study, we observed for the first time that EGFR gene copy number gain was independently associated with poor patient survival of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 56%